Clarification of the diagnosis of the genus Loxosoma s.l. (Entoprocta; Loxosomatidae) based on morphological and molecular data - Borisanova, Anastasia; Schepetov, Dimitry (Zootaxa, 2023)
Loxosomatidae are solitary entoprocts associated with various types of invertebrate hosts. Two genera are distinguished in the family Loxosomatidae, Loxosomella and Loxosoma, that have clear morphological differences in the attachment structures. Loxosoma attaches to the substratum by a muscular sucking pedal disk, which allows moving. Both kidneys and adults are thought to have a pedal disc throughout their lives. In August 2021, several specimens of loxosomatids were found in the White Sea at a depth of 30–70 m on a polychaete Laonice sp. (Spionidae), which were investigated using light and electron microscopy as well as molecular phylogenetic analysis. These loxosomatids were identified as Loxosomella aripes Nielsen, although a stalk of large buds of the specimens from the White Sea terminate with a pedal disc typical of Loxosoma. Molecular phylogenetic analysis of two markers [28S rRNA (~380bp) and 18S rRNA (in three parts totaling ~1850bp)] confirms the affinity of the species to Loxosoma s.l. and does not confirm monophyly of the genera Loxosoma and Loxosomella, indicating that the entire system of loxosomatids requires revision. Here, we redescribe the species Loxosomella aripes as Loxosoma s.l. aripes. The diagnosis of the genus Loxosoma s.l. is supplemented with the observation that the structure of the attachment organ can change after anchoring to the substrate. A list of species currently assigned to Loxosomella that may in fact belong to the genus Loxosoma s.l. is also given.